Addressing Cybercrime in the Sharia Digital Wallet Industry: A Legal Perspective in the Indonesian Context - Hamsin Muhammad Khaeruddin; Halim Abdul; Anggriawan Rizaldy (E3S Web of Conferences, 2023)
The advent of Sharia digital payments in Indonesia's Islamic economics represents a transformative leap. While this innovation offers a plethora of advantages, exercising prudence is imperative, given the potential risks that overlooking certain dimensions might entail, particularly in the realms of cybercrime and data misuse. Critical focal points encompass compliance, security, and the protection of personal data. To tackle these concerns comprehensively, this paper delves into the regulatory landscape governed by the Indonesian government regarding data privacy for users of Islamic e-wallets. Moreover, it navigates through the potential pitfalls and challenges associated with Islamic digital payments, with a spotlight on data safeguarding and the specter of cybercrime. Employing a normative methodology encompassing statutory, case-based, and conceptual approaches, the study reveals that the utilization of Sharia e-wallets in Indonesia harmonizes with the Islamic principles expounded in the Fatwa of the National Sharia Council. The government has further fortified its stance with robust regulations for safeguarding personal data, facilitated by institutional collaboration involving Bank Indonesia and the Financial Services Authority. Nevertheless, diligent attention remains a prerequisite to guarantee the adherence of Sharia digital payment operators to the existing legal framework.